Haunting sex? Capitalism as spectre in the Australian anti-'sexualization of childhood' rhetoric. Issue 6 (2nd November 2018) - Thompson, Jay Daniel
ABSTRACT: This article explores the anti-'sexualization of childhood' rhetoric that has circulated in Australia since the publication of the Corporate Paedophilia report in 2006. I argue that this rhetoric is striking because of how it appears to have moved away from the ostensibly feminist and anti-capitalist stance taken by Corporate Paedophilia, and been advanced by Right-leaning critics (as evidenced by the Safe Schools Coalition Australia controversy of 2016–17). I suggest that this rightward shift can be attributed to two factors. Firstly, within much anti-sexualization rhetoric, capitalism has actually had a spectral presence; it has been hinted at, flagged as being a problem, but seldom been engaged with in any meaningful way. Secondly, anti-sexualization rhetoric has (over)emphasised the relationship between sex and harm, as well as childhood innocence. I suggest that a more nuanced approach to the relationship between childhood, capitalism and sex is needed.